Clinical Outcomes of Fusion in Type II Accessory Naviculars With or Without Asymptomatic Flatfeet. (February 2023) - Sun, Nian; Chen, Junjian; Chen, Zhuhong; Zeng, Canjun; Guo, Hao
Background: Few studies have reported the clinical outcomes of fusion surgeries for type II accessory naviculars. Whether the combination of accessory naviculars and asymptomatic flatfoot will result in worse outcomes in accessory navicular surgeries remains to be elucidated. Our study aims to report the clinical outcomes of fusion for type II accessory naviculars and make a subgroup comparison among accessory navicular patients with or without asymptomatic flatfeet. Methods: From May 2017 to June 2021, all painful type II accessory naviculars with or without asymptomatic flatfeet in our inpatient center were reviewed, and those who only underwent fusion surgeries were included in the retrospective study. Visual analog scale (VAS) scores, American Orthopaedic Foot & Ankle Society (AOFAS) midfoot scores, Tegner activity level scores, complications, patient-reported satisfaction, and imaging results (Meary angle in the weightbearing lateral view, talo–first metatarsal angle and talonavicular coverage angle in the weightbearing anteroposterior view) were used to describe outcomes. Results: Thirty-two eligible patients responded to the latest follow-up request and were included in this study. The mean follow-up duration was 37.1 ± 16.0 months. The average VAS pain score improved from 4.7 ± 1.8 preoperatively to 0.9 ± 1.2 at the latest follow-up ( P <.001). The average AOFAS midfoot score improved from 67.1 ± 8.5 preoperatively to 90.2 ± 10.7 at the latest follow-up ( P <.001). The preoperative and postoperative Tegner activity level scores were similar (3.3 ± 1.5 vs 3.5 ± 1.6, P =.136). The overall complication rate was 37.5%. The most common complication was nonunion (31.3%). The overall satisfaction rate was 90.6%. Similar outcomes were observed between the flatfoot and the nonflatfoot subgroups. Conclusion: Fusion for painful type II accessory naviculars resulted in good symptom relief, function improvement, and patient satisfaction at midterm follow-up, but the nonunion rate was relatively high. Fusion for painful type II accessory naviculars with or without asymptomatic mild to moderate flatfoot brought about similar clinical outcomes. Level of Evidence: Level III, retrospective comparative study.